Penentuan Model Adsorpsi Metil Merah pada Karbon Aktif berbasis Torefaksi Arang Batubara - Indarto, Antonius; Hartanto, Yansen; Putranto, Aditya; Bunaidi, Rendi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
The Rate Determining Step (RDS) in adsorption proses plays a key role in order to understand the correct adsoption mechanism. In this experiment, a simple method used for distinguishing the RDS of liquid adsorption on solid adsorben was studied by an experiment based on Shrinking-Core Diffusion-based Model (SCM). RDS determination was done by comparing experimental data of two SCM Models: (1) Pore-Surface Model Diffusion (PSDM) and (2) Film-Pore Diffusion Model (FPDM). The adsorption of methylene blue by activated carbon obtained from Jatropha curcas L. was used as a case study. The result of experiment by three variated parameters: initial concentration (C0), pH, and type of adsorben shows that PSDM has more accuration compared to FPDM in representating the characterstic of mass transport of metil red adsorption on activated carbon.